The Ivankiad, or, The tale of the writer Voinovich's installation in his new apartment - Vladimir Voinovich ; translated by David Lapeza. (Cape, 1978)
Translation of Ivankiada, ili, Rasskaz o vselenii pisatelia Voinovicha v novuiu kvartiru.